Compulsions of integration - Lewis, Vaughan (West Indian Commission St. MichaelBB, 1992)
Puts forward the view that the progress made towards achieving economic integration has not been significant owing to the failure to establish mechanisms which would ensure that decisions integral to the realisation of that objective, would be enforced in all Member States. Sees meaningful integration as the only way in which the Caribbean can survive as a viable economic entity.